Adding an extra layer of nylon - Mumbai Archive Project Team (Jio Institute, 2024)
Rajesh Pardesi is adding an extra layer of nylon thread to strengthen the net. Net repair is learned through observation and practice, a skill passed down through generations. Rajesh acquired it from his grandfather and father by assisting them from a young age.